PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO RETURN ON EQUITY DAN SALES GROWTH TERHADAP HARGA SAHAM - Made Arvin Ariantara; Ida I Dewa Ayu Mas Manik Sastri; I Wayan Gde Yogiswara Dharma Putra (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2023)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio, Return On Equity and Sales Growth on Stock Prices in Manufacturing Companies in the Consumer Non-Cyclicals Sector Listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The population in this study were 105 companies using a purposive sampling method to determine the sample based on the criteria so that a sample of 40 companies were obtained that met the requirements in this study. The main theories used in this study are agency theory and signaling theory. The data analysis technique used in this study is Multiple Linear Regression Analysis. Based on the results of the analysis that has been carried out, it can be seen that the results of this study are Current Ratio and Return On Equity have a positive and significant effect on stock prices. This indicates if the increase or decrease in the value of the Current Ratio and Return On Equity will affect stock prices. The Debt to Equity Ratio variable has a positive and insignificant effect on stock prices. This indicates that this ratio is not the ratio that investors pay attention to when investing. Meanwhile, Sales Growth has a negative and insignificant effect on stock prices. This indicates that an increase or decrease in the value of Sales Growth will not affect the rise and fall of stock prices